If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6 + 2i)(3 + 6i) = 0 Multiply (6 + 2i) * (3 + 6i) (6(3 + 6i) + 2i * (3 + 6i)) = 0 ((3 * 6 + 6i * 6) + 2i * (3 + 6i)) = 0 ((18 + 36i) + 2i * (3 + 6i)) = 0 (18 + 36i + (3 * 2i + 6i * 2i)) = 0 (18 + 36i + (6i + 12i2)) = 0 Combine like terms: 36i + 6i = 42i (18 + 42i + 12i2) = 0 Solving 18 + 42i + 12i2 = 0 Solving for variable 'i'. Factor out the Greatest Common Factor (GCF), '6'. 6(3 + 7i + 2i2) = 0 Factor a trinomial. 6((3 + i)(1 + 2i)) = 0 Ignore the factor 6.Subproblem 1
Set the factor '(3 + i)' equal to zero and attempt to solve: Simplifying 3 + i = 0 Solving 3 + i = 0 Move all terms containing i to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + i = 0 + -3 Combine like terms: 3 + -3 = 0 0 + i = 0 + -3 i = 0 + -3 Combine like terms: 0 + -3 = -3 i = -3 Simplifying i = -3Subproblem 2
Set the factor '(1 + 2i)' equal to zero and attempt to solve: Simplifying 1 + 2i = 0 Solving 1 + 2i = 0 Move all terms containing i to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 2i = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 2i = 0 + -1 2i = 0 + -1 Combine like terms: 0 + -1 = -1 2i = -1 Divide each side by '2'. i = -0.5 Simplifying i = -0.5Solution
i = {-3, -0.5}
| 8x+11=3x+41 | | y=0.25-1 | | 5.5(x-3)=0.5x+25.5 | | -7(6+5x)=16 | | 2x+7(x-7)=23 | | 4(a-4)+6(a+4)=1(a^2-16) | | p-32=0.6p | | 75-5x=3x-35 | | 13+6x=3x-20 | | (2x+2)/2=-3 | | b=5(9a+2b) | | (2x+2)/2=3 | | -4x+5(x-5)=-19 | | 7.41x+74.1=148.2 | | 6x-4=5-6x+12 | | 15x+13y=162 | | 22=-3(4n+7) | | x-67=-4x+38 | | R=78x-0.4x^2 | | 3(x-2)=6x+6 | | -1=lnx^5 | | 5-3+-1= | | 6.5a+10=68.5 | | 4x+2(-6x+6)=-36 | | 10-4x-x=19 | | 3x+32+5x-6=132 | | n-25=n-3 | | 9x+18=81-3x | | 8x+17=-61+2x | | 50x+100=c | | 15-2x=12+x | | (x+3)+(2x-1)+110=180 |